Analisa In Depth Online Analytical Processing (OLAP) Business Intelligence (BI) dengan Filter Inheritance pada Distribusi Sosial di Kecamatan Setiabudi - Alhadi, Alhadi; Fitri, Iskandar; Andrianingsih, Andrianingsih (KITA Institut, 2021)
A lot of census data in the sub-district is very useful and helps the social service to provide social assistance in a sub-district. With this Business Intelligence system, it can help analyze information on providing social assistance with the help of using the Tableau Tools so that the information is more detailed and displays a graphic / dashboard visualization. This research is to analyze how certain people who receive social assistance for residents of Setiabudi sub-district, and each provision of social assistance will be collected from the sub-district and submitted to each sub-district to be able to data with certainty, using the number of data on the head of the family registered in Setiabudi District.Keywords:Business Intelligence, Tableau Tools, OLAP, Government Agencies.